The Hairdresser of Harare by Tendai Huchu: A hard-hitting etiological critique of the social and political malady bedeviling contemporary Zimbabwe - Babou Ngom, Mamadou Abdou (Advances in Social Sciences Research Journal, 2018)
This research paper sets out to delve into the root causes of the multifaceted woes bedeviling contemporary Zimbabwe through The Hairdresser of Harare by one of present-day Zimbabwe’s most talented and celebrated novelist, Tendai Huchu. The article argues that decades of misrule and its attendant downsides of corrupt practices have brought the country pretty much to its knees. The grassroots fell hard done by as they are reduced to living by their wits in order to get by. Tendai Huch’s lead character and narrator’s repeated flashbacks to the promising beginnings of nationhood and her relentless delivery of strictures on the crass disregard for the law across the board bespeaks a sense of anticlimax over the betrayal of the ideals of the liberation war. The Hairdresser of Harare is a scathing indictment of a deeply failed leadership whose malign backwash effects percolate through every strata of society.